Phenylhydrazine hydrochloride induced dosedependent embryo cytotoxicity in zebrafish - Rajagopal, Raskin Erusan (Bioinformation, 2019)
Phenylhydrazine hydrochloride (PHZ) is a chemical compound. PHZ and its derivatives were used firstly as antipyretics, treatment of blood disorders such as polycythaemia Vera. For many years phenyl hydrazine was used for experimental induction of anaemia in animal models. However, this compound is reported to cause damage to red blood cells, potentially resulting in anaemia and consequential secondary involvement of other tissues, such as the spleen and liver. Recent studies suggest that PHZ cause genotoxicity in mice models. The aim of our study is to study the effect of PHZ in embryonic and larval stage of zebra fish model. Zebra fish embryos and larvae were used in this study. Working concentration prepared from 0.05 gm of PHZ stock solution. The embryos and larvae were exposed to different concentrations of PHZ (0.1, 0.3, 0.5, 0.7 0.9, 1.0, 3.0, 5.0, 7.0 9.0 and 10.0 µg/mL) and (0.1, 0.3, 0.5, 0.7, 0.9 and 1.0 µg/mL) respectively. Survival rate, mortality rate, hatching rate and phenotypic anomalies were studied in developing embryos. Heart rate and apoptosis were evaluated to assess the PHZ toxicity in larval stage of Zebra fish. Statistical analysis was performed by Pearson correlation and P values < 0.05 were considered statistically significant. The LC50of PHZ in embryo and larvae was found to be 0.7µg/mL. PHZ treated embryos showed that survival rate was decreased during 72hpf. In the case of mortality, 0.7 µg/mL and above concentration mortality rate was significantly increased between 48 and 72 hpf and the none embryos survived after 72 hpf. We observed delayed hatching rate in treated embryos when compared to control embryos. 0.5 µg/mL treated larvae showed significantly (p<0.05) decreased heart rate 20% at 96 hrs. Phenotype anomalies such as enlarged yolk sac, yolk sac split, pericardial edema, notochord anomaly appeared at higher concentration of PHZ treated embryos. Acridine orange fluorescence staining revealed that high apoptotic cells were detected at caudal fin region of larvae on day 3 at a concentration of 0.7µg/mL treated group. Our study suggests that PHZ causes multiple phenotypic abnormalities and toxicity on zebrafish embryos and larvae with respect of dose and time dependent manner.